Pathological Gambling in Arrestee Populations in Des Moines, Iowa, and Las Vegas, Nevada, 2000-2001 - McCorkle, Richard ([Verlag nicht ermittelbar], 2003)
This study sought to examine the extent, nature, and consequences of pathological gambling disorders in arrestee populations. Five research questions were addressed: (1) What is the prevalence of pathological gambling in arrestee populations? (2) What is the profile of the pathological gambler arrested for felony and misdemeanor offenses? (3) How does the nature and level of criminal activity among pathological gamblers compare to that of non- pathological gamblers? (4) What proportion of the crime committed by offenders with pathological gambling disorders is linked to their gambling activities (either to fund gambling or pay off gambling debts)? and (5) How does substance abuse interact with pathological gambling to affect the nature and extent of criminal activity? The data for this research were collected in conjunction with the National Institute of Justice's Arrestee Drug Abuse Monitoring (ADAM) programs. Arrestees in Las Vegas, Nevada, and Des Moines, Iowa, who had completed the ADAM interview and provided a urine specimen were asked if they would be willing to answer an additional set of questions concerning their gambling behavior. Data from the ADAM interview and drug screening were merged with data collected using the gambling addendum, producing the dataset for this study. Variables from the ADAM instruments were comprised of demographic data on each arrestee, calendar of admissions to drug treatment-related programs, data on dependence and abuse, drug market and use data, and urine test results. The gambling addendum was used to collect data on five topics: (1) past-year gambling activity, (2) the use of alcohol and illegal drugs prior to and during gambling, (3) substance abuse and/or self-reported gambling problems, (4) past-year criminal activity (property, drug, and violent offending), and (5) motivations for criminal activity (gambling or non-gambling related).